2006
DOI: 10.1371/journal.pgen.0020091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screens for Mutations Affecting Development of Xenopus tropicalis

Abstract: We present here the results of forward and reverse genetic screens for chemically-induced mutations in Xenopus tropicalis. In our forward genetic screen, we have uncovered 77 candidate phenotypes in diverse organogenesis and differentiation processes. Using a gynogenetic screen design, which minimizes time and husbandry space expenditures, we find that if a phenotype is detected in the gynogenetic F2 of a given F1 female twice, it is highly likely to be a heritable abnormality (29/29 cases). We have also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 53 publications
0
72
0
Order By: Relevance
“…Unlike X. laevis, X. tropicalis is being developed as a genetic model organism , and in the future, mutant strains will be available. The genome sequence for this species is already available and both forward and reverse genetic techniques are described for this species (Goda et al, 2006). Forward genetic screens make use of ENU mutagen to create point mutations in sperm.…”
Section: Xenopus Tropicalis: the New Frog In The Pondmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike X. laevis, X. tropicalis is being developed as a genetic model organism , and in the future, mutant strains will be available. The genome sequence for this species is already available and both forward and reverse genetic techniques are described for this species (Goda et al, 2006). Forward genetic screens make use of ENU mutagen to create point mutations in sperm.…”
Section: Xenopus Tropicalis: the New Frog In The Pondmentioning
confidence: 99%
“…Female F1 carriers of the mutations are then used to produce gynogenetic diploid F2 animals enabling faster screening of recessive phenotypes. The reverse genetic technique TILLING (targeting induced local lesions in genomes) method has been used to detect mutations in specific genes and is also amenable to large-scale mutant production (Goda et al, 2006). Insertional mutation strategies that take advantage of transposable elements are also being pursued (Yergeau and Mead, 2007).…”
Section: Xenopus Tropicalis: the New Frog In The Pondmentioning
confidence: 99%
“…In contrast to t e × l s hybrids that die as embryos, haploid Xenopus embryos develop to the tadpole stage 8,9 , suggesting that hybrid death is due to factors brought in by the X. laevis sperm to the X. tropicalis egg during fertilization. Irradiation of X. laevis sperm prior to fertilization, which destroys the DNA 10,11 , resulted in a haploid phenotype (Fig. 1e and Videos 3, 4), indicating that t e × l s embryo death is due to the presence of the X. laevis genome.…”
mentioning
confidence: 95%
“…However, until recently, chemical genetic screens had not been carried out in Xenopus embryos, and screens using zebrafish have led the way in vertebrates. In recent years, the use of genetics in Xenopus tropicalis (Goda et al, 2006) and work by the authors and others in chemical genetic phenotypic screens have shown Xenopus to be an excellent model system for such screens Longo et al, 2008;Tomlinson et al, 2005Tomlinson et al, , 2009aWheeler and Brandli, 2009). In fact, Xenopus is the only tetrapod vertebrate to have free-living embryos in which embryonic development is neither in utero nor in ovo and thus is the highest order in which highthroughput screens can be carried out (Wheeler and Brandli, 2009).…”
Section: Setting Up Chemical Genetic Screensmentioning
confidence: 99%